Proteomic profiling of N‐linked glycoproteins identifies ConA‐binding procathepsin D as a novel serum biomarker for hepatocellular carcinoma. Issue 2 (February 2014) - Qi, Yi‐Jun; Ward, Douglas G.; Pang, Chun; Wang, Qi‐Ming; Wei, Wenbin; Ma, Jin; Zhang, Juan; Lou, Qiang; Shimwell, Neil J.; Martin, Ashley; Wong, Nathalie; Chao, Wei‐Xia; et al.
<x xml:space="preserve">Abstract</x> The aim of this study was to identify novel biomarkers for the diagnosis of, and potential therapeutic targets for, hepatocellular carcinoma (HCC). Multilectin affinity chromatography was used to enrich N‐linked glycoproteins from nontumorous liver and HCC tissues followed by 2DE and protein identification by MS. Twenty‐eight differentially expressed proteins were identified. Western blotting validated consistently lower concentrations of human liver carboxylesterase 1 and haptoglobin, and higher concentration of procathepsin D (pCD) in HCC tissues. Knockdown of cathepsin D (CD) expression mediated by siRNA significantly inhibited the in vitro invasion of two HCC cell lines, SNU449 and SNU473, which normally secrete high‐levels of CD. Prefractionation using individual lectins demonstrated an elevation in ConA‐binding glycoforms of proCD and CD in HCC tissues. In the serum of HCC patients, "ConA‐binding proCD" (ConA‐pCD) is significantly increased in concentration and this increase is comprised of several distinct upregulated acidic isoforms (pI 4.5–5.5). Receiver operating characteristic analysis showed that the sensitivity and specificity of serum ConA‐pCD for HCC diagnosis were 85% and 80%, respectively. This is the first report that serum ConA‐pCD is increased significantly in HCC and is potentially useful as a serological biomarker for diagnosis of HCC.